Acoustic cues for the recognition of self-voice and other-voice - Xu, Mingdi; Homae, Fumitaka; Hashimoto, Ryu-ichiro; Hagiwara, Hiroko (Frontiers in Psychology, 2013)
Self-recognition, being indispensable for successful social communication, has become a major focus in current social neuroscience. The physical aspects of the self are most typically manifested in the face and voice. Compared with the wealth of studies on self-face recognition, self-voice recognition (SVR) has not gained much attention. Converging evidence has suggested that the fundamental frequency (F0) and formant structures serve as the key acoustic cues for other-voice recognition (OVR). However, little is known about which, and how, acoustic cues are utilized for SVR as opposed to OVR. To address this question, we independently manipulated the F0 and formant information of recorded voices and investigated their contributions to SVR and OVR. Japanese participants were presented with recorded vocal stimuli and were asked to identify the speaker—either themselves or one of their peers. Six groups of 5 peers of the same sex participated in the study. Under conditions where the formant information was fully preserved and where only the frequencies lower than the third formant (F3) were retained, accuracies of SVR deteriorated significantly with the modulation of the F0, and the results were comparable for OVR. By contrast, under a condition where only the frequencies higher than F3 were retained, the accuracy of SVR was significantly higher than that of OVR throughout the range of F0 modulations, and the F0 scarcely affected the accuracies of SVR and OVR. Our results indicate that while both F0 and formant information are involved in SVR, as well as in OVR, the advantage of SVR is manifested only when major formant information for speech intelligibility is absent. These findings imply the robustness of self-voice representation, possibly by virtue of auditory familiarity and other factors such as its association with motor/articulatory representation.